The Effects of Fermentation Extent and Acid Concentration on Bioethanol from HVS Paper Waste - Rizka Mulyawan; Rizka Nurlaila; Tsa Tsa Anindya Rakhim Ahmadi; Muhammad Muhammad; Novi Sylvia; Agam Muarif (Program studi Teknik Kimia UNS, 2023)
Abstract. Bioethanol is an alternative energy sourced from environmentally friendly raw materials from wastes that contain a lot of lignocellulosic such as HVS paper. Paper contains about 85% cellulose, 8% hemicellulose, 5% lignin and the rest is in the form of ash compounds. Bioethanol is ethanol produced from the fermentation of glucose (sugar) followed by a distillation process. This study aims to analyze the effect of a combination of fermentation time and concentration of sulfuric acid on bioethanol. The highest yield of beathanol was obtained at a hydrolysis concentration of 6.5% with a 7-day fermentation time of 3.45%. Bioethanol density that was close to standard was 3.5% acid concentration with 3 and 5 days fermentation. Moreover, at 3.5% acid concentration showed the closest bioethanol viscosity to the standard value with all conditions synthesized acidic bioethanol with pH ranged from 6 to 6.5Keywords:Bioethanol, Fermentation, HVS paper, Sulfuric acid